Blastic plasmacytoid dendritic cell neoplasm: clinical features in 90 patients. (30th August 2013) - Julia, F.; Petrella, T.; Beylot‐Barry, M.; Bagot, M.; Lipsker, D.; Machet, L.; Joly, P.; Dereure, O.; Wetterwald, M.; d'Incan, M.; Grange, F.; Cornillon, J.; et al.
Abstract : What's already known about this topic? Cutaneous spreading of blastic plasmacytoid dendritic cell neoplasm (BPDCN) has initially been reported as diffuse bruise‐like macules. It may also present as an isolated tumoral nodule, a bruise‐like macule, or an association of both. What does this study add? This series of 90 patients with BPDCN helps to clarify the different clinical presentations. Three groups emerged from this study: the nodular form is the most frequent clinical subtype, bruise‐like lesions represent a clinical pitfall, and disseminated lesions are the most suggestive clinical presentation. However, the clinical presentation is not a relevant prognosis factor. Summary: Background: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare disease characterized by malignant proliferation of a contingent blastic plasmacytoid dendritic cell. This rare entity is recognized mostly by cutaneous spreading, or not having a leukaemic component. The prognosis is very poor. Objectives: To study a large cohort of 90 patients with BPDCN, to define additional symptoms to form a correct diagnosis earlier, and to manage such patients accordingly. Methods: We retrospectively reviewed BPDCN cases registered in the French Study Group on Cutaneous Lymphoma database between November 1995 and January 2012. Ninety patients were studied. Demographic data, clinical presentation, initial staging and outcome were recorded. Results: The group contained 62 male and 28 female patients (sex ratio 2·2). Their ages ranged from 8 to 103 years at the time of diagnosis (mean 67·2 years). Three major different clinical presentations were identified. Sixty‐six patients (73%) presented with nodular lesions only, 11 patients (12%) with 'bruise‐like' patches and 13 (14%) with disseminated lesions (patches and nodules). Mucosal lesions were seen in five patients (6%). The median survival in patients with BPDCN was 12 months. Conclusions: We here distinguish three different clinical presentations of BPDCN. A nodular pattern is a more common feature than the originally reported 'bruise‐like' pattern. Despite the fact that BPDCN may initially appear as a localized skin tumour, aggressive management including allogeneic bone marrow transplantation should be considered immediately, as it is currently the only option associated with long‐term survival.